2007
DOI: 10.1152/ajprenal.00473.2006
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of organic anion transporters OAT1 and OAT3 correlates with impaired secretion ofpara-aminohippurate after ischemic acute renal failure in rats

Abstract: M. Downregulation of organic anion transporters OAT1 and OAT3 correlates with impaired secretion of para-aminohippurate after ischemic acute renal failure in rats. Am J Physiol Renal Physiol 292: F1599 -F1605, 2007. First published January 23, 2007; doi:10.1152/ajprenal.00473.2006.-Ischemic acute renal failure (iARF) was described to reduce renal extraction of the organic anion para-aminohippurate (PAH) in humans. The rate-limiting step of renal organic anion secretion is its basolateral uptake into proximal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
88
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 38 publications
11
88
1
Order By: Relevance
“…No other studies have assessed such post-renal obstruction with regard to OAT expression; however, investigations have evaluated the effects of ischemia-reperfusion injury on renal OAT expression/function. In two such studies, it was reported that ischemia-reperfusion injury decreased mRNA and protein expression of both rOat1 and rOat3 [111,112]. Supporting this finding, either PAH clearance was reduced [111], or indoxyl sulfate serum levels were increased with a concomitant decrease in basolateral transport of PAH and estone sulfate [112].…”
Section: Phosphorylationmentioning
confidence: 84%
See 2 more Smart Citations
“…No other studies have assessed such post-renal obstruction with regard to OAT expression; however, investigations have evaluated the effects of ischemia-reperfusion injury on renal OAT expression/function. In two such studies, it was reported that ischemia-reperfusion injury decreased mRNA and protein expression of both rOat1 and rOat3 [111,112]. Supporting this finding, either PAH clearance was reduced [111], or indoxyl sulfate serum levels were increased with a concomitant decrease in basolateral transport of PAH and estone sulfate [112].…”
Section: Phosphorylationmentioning
confidence: 84%
“…In two such studies, it was reported that ischemia-reperfusion injury decreased mRNA and protein expression of both rOat1 and rOat3 [111,112]. Supporting this finding, either PAH clearance was reduced [111], or indoxyl sulfate serum levels were increased with a concomitant decrease in basolateral transport of PAH and estone sulfate [112]. Indoxyl sulfate is a known OAT substrate and uremic toxin.…”
Section: Phosphorylationmentioning
confidence: 85%
See 1 more Smart Citation
“…25,26 Similarly, decreased human (h)OAT1, or rOat1 and rOat3, protein expression was observed in acute renal failure patients or animals with experimentally induced acute renal failure. [27][28][29][30] Renal proximal tubule cell loss owing to injury is likely a major contributing factor to this decrease in total protein expression level.…”
Section: Oats As Determinants In Tubular Secretion Of Uremic Toxinsmentioning
confidence: 99%
“…5,6) It has been shown that the expression of transporters was altered in the organ after I/R. [7][8][9][10] I/R can occur in many organs, including intestine, liver and kidney. The intestine, liver and kidney play a principal role in the absorption and excretion of a wide variety of xenobiotics, including drugs and toxins, as well as endogenous compounds.…”
mentioning
confidence: 99%